PENGARUH BIMBINGAN MENTAL UNTUK MENINGKATKAN SELF-ESTEEM PADA LANJUT USIA DEPRESI DI PANTI TRESNA WERDHA HARGO DEDALI SURABAYA - Sofina Palamani; Muljono Muljono; Marlina Marlina (POLTEKKES KEMENKES MANADO, 2012)
Aging or process of being old is a process of gradual disappearance of the ability body tissues to repairthemselves or replace and maintain normal function and so can not survive against infection, is todarmage suffered. Along with the aging process, the body will experience a variety of problems orcommonly relerred to as regenerative didease. The accumulation of a lifetime of depressing event, such asbereavement, painful illness, losing of job, loneliness,, institutionalization, etc. Will cause depression inthe elderly. The objective of this studi was to investigate the influence of mental guidance to the reductionof the level of elderly’s depression in Hargo Dedali Folk’s Home Surabaya. This research design is quasyexperiment. Samples are chozen by two stage random sampling from homogene population. Ten sessioneach one hour for 10 elders in the experimental group and another 10 elders were recruited for controlgroup matched to experiment subjects on relevant criteria. Data collected by questionnaire with GeriatricDepression Scale (GDS) and Self-esteem Quiz (SEQ) and then analyzed by statistic non parametic withcomputer software SPSS 15.0 for windows. Result of these research shows that mental guidanceis good.The difference of the level of depression before and after giving treatment is having decrease significantlyin difference in the treatment and control score p =S 0.032, difference in the treatment prettest andposttest score (p = 0.034), difference in the treatment and control (self-esteem) score p = 0.003, differencein the pretest and posttest (self-esteem) score p = 0.008. The result of statistic above had been indicatingthat mental guidance will decrease the level of elderly’s depression and the raising elderly;s self-esteem. Itcan be concluded that mental guidance is effective for helping depressive elderly to cope with theirproblem. It is should be recommended for caregiver and the family in folk’s home or community, to heldthe mental guidance to overcome the depression problem in the elderly, make them feel worthy as ahuman being and to fulfill their need to be care, to be heard, leave their legali for the younger generation,and can be increase quality of life of elderly